THE PORTRAYAL OF INTERNAL MIGRATION IN UZBEK LITERATURE: HISTORICAL CONTEXT AND AESTHETIC INTERPRETATION - Namazova Manzura Urakovna (Journal of Applied Science and Social Science, 2026)
This article provides a comprehensive examination of internal migration in Uzbek literature. Internal migration is defined as intranational population movement, primarily from rural to urban areas. The study analyzes this phenomenon across two distinct historical periods: the Soviet era (1930-1980) and the post-independence period (1991-present). The research employs narrative analysis and psychological-interpretive methods to trace the transformation of internal migration from a symbol of socialist progress into a source of economic and psychological suffering. The article identifies four key thematic patterns: rural-urban cultural conflict, nostalgia and contradictory desire, identity crisis, and social criticism. The study applies Homi Bhabha’s concept of «third space» to reveal both distinctively local characteristics and emerging global resonances. The research demonstrates that internal migration literature serves a crucial social function by exposing the internal psychological dimensions of migration alongside its external manifestations. The study concludes that younger generation writers (2010-2020) are increasingly incorporating hybrid identity and environmental factors into this established literary tradition.